2013
DOI: 10.3109/09637486.2013.849662
|View full text |Cite
|
Sign up to set email alerts
|

Dietary strategies to recover from exercise-induced muscle damage

Abstract: Exhaustive or unaccustomed intense exercise can cause exercise-induced muscle damage (EIMD) and its undesirable consequences may decrease the ability to exercise and to adhere to a training programme. This review briefly summarises the muscle damage process, focusing predominantly on oxidative stress and inflammation as contributing factors, and describes how nutrition may be positively used to recover from EIMD. The combined intake of carbohydrates and proteins and the use of antioxidants and/or anti-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 179 publications
0
75
0
8
Order By: Relevance
“…Studies examining the acute effect of RE on inflammatory markers revealed significant elevations [5,6] and no changes [2,7] in inflammatory cytokines. The inflammatory responses to a single bout of RE may be due to RE-induced muscle damage [8]. In addition to muscle damage, RE may trigger cytokine production by other physiological factors such as neuroendocrinological factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the acute effect of RE on inflammatory markers revealed significant elevations [5,6] and no changes [2,7] in inflammatory cytokines. The inflammatory responses to a single bout of RE may be due to RE-induced muscle damage [8]. In addition to muscle damage, RE may trigger cytokine production by other physiological factors such as neuroendocrinological factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is equivocal as to whether beetroot juice and/or its constituents are effective AOXs, with some studies suggesting not (Whitfield et al, 2016;Larsen et al, 2014) and others showing reductions in oxidative stress and inflammatory markers (Clifford et al 2015;El Gamal et al 2014;Jadert et al 2012;Justice et al 2015;Pietrzkowski et al 2010;Ashor et al, 2016). Notwithstanding the disparate findings to date, it is conceivable that AOX or anti-inflammatory effects could help to dampen the acute secondary muscle damage response after an exercise bout-the hallmarks of which are proposed to be oxidative stress, inflammation and muscle proteolysis-and this could facilitate a faster recovery of muscle function and/or reduction in muscle pain (Howatson & van Someren, 2008;Sousa et al 2014;Urso 2013). Indeed, these are the proposed mechanisms that underpin the effects seen with other functional foods on recovery after muscle-damaging exercise (Howatson et al 2010;Trombold et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These foods are proposed to provide an additional value beyond their caloric content that might be beneficial for health and well-being (Corbo et al 2014). This interest stems from the observation that some functional foods contain a variety of naturally occurring compounds, such as polyphenols (Myburgh 2014), which appear to exhibit a broad range of physiological benefits that include, but are not limited to, antioxidant (AOX) and antiinflammatory effects (Nikolaidis et al 2012;Sousa et al 2014). There are now several reports that supplements rich in these phytonutrients, such as Montmorency cherry juice (Howatson et al 2010;Bowtell et al 2011;Bell et al 2014;Bell et al 2015), blueberry juice (McLeay et al 2012), and pomegranate juice (Trombold et al 2010;Trombold et al 2011) can attenuate indices of EIMD and accelerate recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the anti-inflammatory effects of so-called functional foods for the purpose of enhancing exercise recovery (Myburgh 2014;Sousa et al 2014). These foods are proposed to provide an additional value beyond their caloric content that might be beneficial for health and well-being (Corbo et al 2014).…”
Section: Introductionmentioning
confidence: 99%